2011
DOI: 10.1038/onc.2011.32
|View full text |Cite
|
Sign up to set email alerts
|

The HDAC class I-specific inhibitor entinostat (MS-275) effectively relieves epigenetic silencing of the LAT2 gene mediated by AML1/ETO

Abstract: The chromosomal translocation (8;21) fuses the hematopoietic transcription factor AML1 (RUNX1) with ETO (RUNX1T1, MTG8), resulting in the leukemia-specific chimeric protein AML1/ETO. This fusion protein has been implicated in epigenetic silencing, recruiting histone deacetylases (HDACs) and DNA methyltransferases to target promoters. Previously, we have identified a novel in vivo AML1/ETO target gene, LAT2 (NTAL/LAB/ WBSCR5), which is involved in FceR I, c-Kit, B-cell and T-cell receptor signalling. We have no… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
33
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 45 publications
(34 citation statements)
references
References 52 publications
1
33
0
Order By: Relevance
“…In agreement with these results, a recent paper demonstrated that mocetinostat and entinostat, but not TSA or sodium valproate, increased the expression of LAT2, which is a target of AML1-ETO. 32 Our results raise the possibility that treatment with certain HDACi may be effective in AML patients bearing these fusion proteins. Such treatment can be combined with ATRA in case of acute promyelocytic leukemia (the AML type that is associated with PML-RARA), especially because we found that ATRA alone does not reverse the downregulation of CD48.…”
Section: Discussionmentioning
confidence: 66%
See 3 more Smart Citations
“…In agreement with these results, a recent paper demonstrated that mocetinostat and entinostat, but not TSA or sodium valproate, increased the expression of LAT2, which is a target of AML1-ETO. 32 Our results raise the possibility that treatment with certain HDACi may be effective in AML patients bearing these fusion proteins. Such treatment can be combined with ATRA in case of acute promyelocytic leukemia (the AML type that is associated with PML-RARA), especially because we found that ATRA alone does not reverse the downregulation of CD48.…”
Section: Discussionmentioning
confidence: 66%
“…32 Importantly, the predicted sequence of the binding site of AML1-ETO in the CD48 gene, as well as LAT2, were significantly enriched both with the anti-ETO and the anti-AML1-ETO antibodies compared with the control anti-HA mAb and to the unrelated site ( Figure 6G). These experiments verify that indeed, AML1-ETO binds directly to the CD48 gene.…”
Section: 49mentioning
confidence: 96%
See 2 more Smart Citations
“…On the basis of our analysis, we propose a model of interactions (Fig. 4) based on both previous data (18)(19)(20)(21)(22)(23)(24)(25)(26)(27)(28)(29) and the interactions we found. This example provides evidence that our approach has identified "-omic" linkages that, although new, have basis in biochemical rationale and are supported, in part, by past research (18)(19)(20)(21)(22)(23)(24)(25)(26)(27)(28)(29).…”
Section: Discussionmentioning
confidence: 99%